Distinct functions of chemokine receptor axes in the atherogenic mobilization and recruitment of classical monocytes. Issue 3 (18th February 2013) - Soehnlein, Oliver; Drechsler, Maik; Döring, Yvonne; Lievens, Dirk; Hartwig, Helene; Kemmerich, Klaus; Ortega‐Gómez, Almudena; Mandl, Manuela; Vijayan, Santosh; Projahn, Delia; Garlichs, Christoph D.; Koenen, Rory R.; et al.
Abstract We used a novel approach of cytostatically induced leucocyte depletion and subsequent reconstitution with leucocytes deprived of classical (inflammatory/Gr1hi) or non‐classical (resident/Gr1lo) monocytes to dissect their differential role in atheroprogression under high‐fat diet (HFD). Apolipoprotein E‐deficient (Apoe−/−) mice lacking classical but not non‐classical monocytes displayed reduced lesion size and macrophage and apoptotic cell content. Conversely, HFD induced a selective expansion of classical monocytes in blood and bone marrow. Increased CXCL1 levels accompanied by higher expression of its receptor CXCR2 on classical monocytes and inhibition of monocytosis by CXCL1‐neutralization indicated a preferential role for the CXCL1/CXCR2 axis in mobilizing classical monocytes during hypercholesterolemia. Studies correlating circulating and lesional classical monocytes in gene‐deficient Apoe−/− mice, adoptive transfer of gene‐deficient cells and pharmacological modulation during intravital microscopy of the carotid artery revealed a crucial function of CCR1 and CCR5 but not CCR2 or CX3CR1 in classical monocyte recruitment to atherosclerotic vessels. Collectively, these data establish the impact of classical monocytes on atheroprogression, identify a sequential role of CXCL1 in their mobilization and CCR1/CCR5 in their recruitment.